Reconstruction of faults in elastic half space from surface measurements. (5th April 2017) - Volkov, Darko; Voisin, Christophe; Ionescu, Ioan R
Abstract: We study in this paper a half-space linear elasticity model for surface displacements caused by slip along underground faults. We prove uniqueness of the fault location and (piecewise-planar) geometry and of the slip field for a given surface displacement field. We then introduce a reconstruction algorithm for the realistic case where only a finite number of surface measurements are available. After showing how this algorithm performs on simulated data and assessing the effect of noise, we apply it to measured data. The data were recorded during slow slip events in Guerrero, Mexico. Since this is a well studied subduction zone, it is possible to compare our inferred fault geometry to other reconstructions (obtained using different techniques) found in the literature.